Social media influence and sexual content: A perception study on sexual behaviour among generation Z - Chua, Zi Le; Phang, Chi Yee; Tan, Li Wen; Tang, Wei Kang; Yap, Hao Yi (2023)
Recently, there was a rising social problem, especially in terms of sexual behaviours among Malaysian youths. Social media has lots of policies and rules to ban sexual content. However, there was still a high risk of vulnerability. Thus, this problem should gain the attention of the public. Besides, there was a rise of a new community group on social media that focused on promoting sexual content. This study was guided by the Media dependency Theory and proposed an effective framework to know the perception of Generation Z on sexual behaviours. To know the perception of Generation Z towards sexual content on social media and to examine the effect of sexual content in social media on sexual behaviours among Generation Z, an online survey was conducted among 384 Malaysian undergraduate students. IBM Statistical Package for the Social Sciences (SPSS) Version 29 was used for data analysis. The findings showed that Generation Z still cannot differentiate sexual behaviours and sexual misconduct. Besides, even though Generation Z was exposed to various sexual content, most of them will not engage in sexual behaviours. This study can provide descriptive information for Malaysian researchers or authorities to have a reference on the perception study of sexual behaviours and help the social media giants to generate stricter rules and regulations